Time-motion characteristics and physiological responses of para-footballers with cerebral palsy in two small-sided games and a simulated game - Henríquez, M.; Iturricastillo, A.; González-Olguín, A.; Herrera, F.; Riquelme, S.; Reina, R. (Adapted Physical Activity Quarterly, 2023)
This study compared physical performance in a group of international cerebral palsy football players during two formats of small-sided games (SSGs) and performance in a simulated game (SG) according to players` sport classes (FT1, FT2, and FT3). Internal load (heart rate and rating of perceived exertion) and external load (total distance, distance covered at different velocities, maximum speed reached, acceleration, and deceleration) were obtained with global positioning system devices during two formats of SSGs (2-a-side/SSG2 and 4-a-side/SSG4) and an SG (7-a-side). SSG2 demands faster actions compared with SSG4/SG, and significant differences and large effect sizes were found in the distance covered in Speed Zones 5 (16.0-17.9 km/hr) and 6 (>18.0 km/hr; p < .05; .35<2 p <.50, large). Lower moderate accelerations and decelerations per minute in SSG4/SG compared with SSG2 were also found (p < .01; .77<2p<.81, large). In the SSG2 task, the FT3 players reached maximum speeds, covered more distance at the highest intensities, and performed more moderate/high accelerations/decelerations and more sprints compared with FT1 and FT2 players (p < .05; -0.85 < dg < -4.64, large). The SSG2 task could be the best option for discriminating physical demands in important variables for cerebral palsy football performance between classes FT3 versus FT1/FT2.